Intimate video? Creative bodies in the age of the selfie. Issue 1 (2nd January 2016) - Jurriëns, Edwin
Abstract : This article critically examines and reinterprets the key characteristics associated with the contemporary medium of video, such as accessibility, connectivity and reflexivity. By analyzing various video genres and developments in the specific context of Indonesia, it explores to what extent local video users obtain a sense of agency and intimacy in dealing with the medium. It specifically focusses on the way in which the medium enables or obstructs people to have access to information and communication, reflect on social and personal issues and engage in aesthetic exploration. It examines these three different aspects of agency and intimacy by looking at bodily (self-)representations in commercial, home and art video genres. By demonstrating that bodily (self-)representations constitute a substantial part of the development of video in Indonesia, it provides a model for filling the gaps in the hitherto largely unexplored site-specific history of the medium. A special attention is paid to a recent work of the Indonesian video art pioneer, Krisna Murti, in which the representations of the artist's own body are a central theme. The article shows how the work done by Murti puts forward the aesthetic modulation of a video as a way of safeguarding or recuperating agency and intimacy in contemporary information and communication society.